Owner-driver schemes and productivity - Alan Fitz-Patrick; Frank M. Horwitz (South African Journal of Business Management, 1999)
Owner-driver schemes are being introduced by companies wanting productivity improvements in the distribution of their products. This article examines motivating factors for owner-driver schemes and evaluates findings from interview-based research. It also examines factors relating to owner-driver schemes and productivity improvement and identifies Issues concerning their design, implementation and management. Findings suggest that owner-driver schemes improve productivity and that key factors concur with a model of the motivational cycle underlying implementation of owner-driver schemes.
Keywords: 650